Designing Timber Tracking Application by Using ASP.Net and Web Service as Instrument of Timber Legality Assurance System - Ririn Widyastuti; Didiek Sri Wiyono; Wahyudi Sutopo (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
Timber Legality Assurance System (TLAS) is a regulation which provided to prevent illegal logging. The system insists the furniture manufacturers have certification of timber used for their production. They must ensure that the raw materials (log) that used are legal and traceable. Timber Tracking’s services are designed by using ASP.NET Web Service Technology which uses SOAP protocol and WSDL interface so it can be used for multi platform system to system communication which using HTTP protocol. The database of Timber Tracking is designed by using Microsoft SQL Server DBMS which has fully compatibility with other applications that made by ASP.NET framework. Object oriented C# is needed to make the application for client side. The Web Service services has been integrated with Timber Tracking Application which based on desktop application, so it would be accessed easily, and it can be used to help maintain and manage the Timber Legality Verification System variables.